Physicians' Knowledge of Theophylline Use: A Cross-Sectional Study from Jordan: Jordanian Physicians' Knowledge of Theophylline Use. - Ali, Tasneem Basheer; Almomani, Huda Yousef; Al-Tarawneh, Fatima Mahmoud; Alwadi, Maysa Waddah; Suliman, Ahmad Shaher (Jordan Journal of Pharmaceutical Sciences, 2023)
Objective: This cross-sectional study aims to assess physicians' knowledge regarding theophylline drug and other related characteristics in Jordan. Materials and Method: The study was conducted prospectively among physicians in Jordan. Physicians were interviewed using an online questionnaire consisting of two sections. The first section included demographics and other relevant characteristics, while the second section comprised questions about theophylline drug. Results: A total of 385 participants completed the questionnaire. The majority of participants knew that theophylline is used in clinical practice as a bronchodilator (75.6%). Nearly 39% of participants knew that theophylline can be administered orally and intravenously. The largest share of participants (76.1%) did not know that theophylline dosage is calculated based on ideal body weight. Sixty percent of participants knew that theophylline use was not contraindicated during pregnancy. On the other hand, only 27.3% knew that theophylline use was not contraindicated during breastfeeding. The majority of participants (76.1%) had an overall intermediate knowledge of theophylline. Conclusions: It was noted that physicians had an overall intermediate knowledge of theophylline. Physicians demonstrated unsatisfactory knowledge about theophylline’s indications, clinical use, administration, adverse effects, and other related aspects. These findings highlight the need for educational interventions and training programs to improve physicians’ knowledge of theophylline and enhance its effective and safe use in clinical practice.